False reactive HIV-1 diagnostic test results in an individual from Kenya on multiple testing platforms-A case report - Jew Ochola; Michelle Imbach; Leigh Anne Eller; Mark de Souza; Chiaka Nwoga; June Doryne Otieno; Lucas Otieno; Eric Rono; Edwin Kamau; Trevor A. Crowell; John Kevin Owuoth; Christina S. Polyak; et al. (IDCases, 2021)
Background: Rapid diagnostic tests (RDT) are routinely used in screening for HIV infection. More complex diagnostic algorithms incorporating fourth-generation screening and confirmatory HIV-1/HIV-2 differentiation immunoassays (IA) may be used to confirm HIV infection. Co-infections and autoimmune diseases may lead to falsely reactive HIV diagnostic test results. Case presentation: A Kenyan man with asymptomatic schistosomiasis and low risk factors for HIV infection demonstrated an inconsistent and discordant pattern of reactivity on HIV RDT, repeated reactivity on fourth-generation IA and positive at a single time-point for HIV-1 on the Geenius HIV1/HIV2 confirmatory assay during the course of a prospective cohort study with HIV repeat testing. The individual initiated antiretroviral therapy following HIV diagnosis. However, his bi-annual behavioral questionnaire suggested low-risk factors for infection. Supplementary confirmatory serologic and nucleic acid tests were performed and gave discordant results. The participant was determined to be HIV uninfected using cell-associated HIV-1 DNA/RNA testing and antiretroviral therapy was discontinued. Discussion and conclusions: Sole reliance on diagnostic test results may result in misdiagnosis of HIV infection, social harm and potential antiretroviral induced drug toxicity. Interpretation of HIV test results should incorporate multiple parameters.